Penentuan Cadangan Premi Asuransi Jiwa Dwiguna Menggunakan Metode Full Preliminary Term - Sagari, Lujiana; Yurniati, Yurniati; Muchlian, Melvi (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Dual-purpose life insurance is insurance that provides two benefits, where the company will provide compensation if the insured remains alive at the end of the policy period or dies within the policy period. In two-purpose life insurance, insurance participants either die or survive will be paid the sum insured by the insurance company and insurance participants have an obligation to pay a certain amount of money to the insurance company called premiums.This study aims to calculate the amount of premium reserves for two-purpose life insurance using the full preliminary term method. This premium reserve calculation uses the 2019 Indonesian Mortality Table with an interest rate of 5.75%. Based on calculations using the full preliminary term method, the first year premium reserve value is zero. The results of the calculation of endowment life insurance premium reserves using the full preliminary term method in the 10th year of the premium reserve are equal to the amount of compensation provided.